Perspective of Attending Physicians on the Use of Telemedicine in an Outpatient Arthroplasty Setting During the COVID-19 Pandemic. Issue 1 (February 2021) - Kolin, David A.; Carroll, Kaitlin M.; Plancher, Kevin; Cushner, Fred
Background : During the worldwide COVID-19 pandemic, physicians had to improvise and adapt new ways to provide care to patients. Purposes : The purpose of this study was to assess physicians' sentiments regarding telemedicine and its use in orthopedic practices. Methods : We performed a cross-sectional study of attending orthopedic physicians, the majority of whom integrated telemedicine into their practices from March to October 2020. A survey was sent to 517 physicians who had registered for an orthopedics conference. The survey included questions pertaining to various factors regarding telemedicine and each physician's practice. Results : Of the 517 physicians who received the survey, 328 responded, for a 63.4% response rate. Of the 328 respondents, 84.1% did not use telemedicine in their practice prior to the COVID-19 pandemic. Even during the pandemic, the physicians most commonly responded that less than 5% of their practice was conducted by telemedicine (n = 103, 31.4%). The second most common response was that more than 20% of visits were done via telemedicine (n = 72, 22.0%); 43.0% of physicians noted that they would not use telemedicine technology in their practice after the pandemic, but 59.1% of physicians would be willing to do annual visits by telemedicine. Ability to examine the patient (2.0 ± 1.0) was rated worse, overall, than either the experience using the technology (3.2 ± 1.0) or the capacity to communicate with the patient (3.6 ± 1.0). Conclusions : Our survey of orthopedic surgeons demonstrates that while the use of telemedicine technology was minimal prior to the pandemic, its use was widely adopted during the pandemic. Nearly half of physicians said that they will continue to use telemedicine.